Super‐optimal temperatures are detrimental to peanut ( Arachis hypogaea L.) reproductive processes and yield at both ambient and elevated carbon dioxide - P. V. Vara Prasad; Kenneth J. Boote; L. Hartwell Allen; Jean M. G. Thomas (Global Change Biology, 2003)
Continuing increases in atmospheric carbon dioxide concentration (CO 2 ) will likely be accompanied by global warming. Our research objectives were (a) to determine the effects of season‐long exposure to daytime maximum/nighttime minimum temperatures of 32/22, 36/26, 40/30 and 44/34°C at ambient (350 μmol mol −1 ) and elevated (700 μmol mol −1 ) CO 2 on reproductive processes and yield of peanut, and (b) to evaluate whether the higher photosynthetic rates and vegetative growth at elevated CO 2 will negate the detrimental effects of high temperature on reproductive processes and yield. Doubling of CO 2 increased leaf photosynthesis and seed yield by 27% and 30%, respectively, averaged across all temperatures. There were no effects of elevated CO 2 on pollen viability, seed‐set, seed number per pod, seed size, harvest index or shelling percentage. At ambient CO 2 , seed yield decreased progressively by 14%, 59% and 90% as temperature increased from 32/22 to 36/26, 40/30 and 44/34°C, respectively. Similar percentage decreases in seed yield occurred at temperatures above 32/22°C at elevated CO 2 despite greater photosynthesis and vegetative growth. Decreased seed yields at high temperature were a result of lower seed‐set due to poor pollen viability, and smaller seed size due to decreased seed growth rates and decreased shelling percentages. Seed harvest index decreased from 0.41 to 0.05 as temperature increased from 32/22 to 44/34°C under both ambient and elevated CO 2 . We conclude that there are no beneficial interactions between elevated CO 2 and temperature, and that seed yield of peanut will decrease under future warmer climates, particularly in regions where present temperatures are near or above optimum.